2019
DOI: 10.1111/jan.13904
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention climate and its influence on nursing students’ compliance with standard precautions

Abstract: Aim This study examined the influence of the training hospital's infection prevention climate on the nursing students’ compliance with standard precautions during clinical training. Background The concept of infection prevention climate has emerged in healthcare facilities due to the acknowledged influence of organizational culture on the compliance of healthcare workers on infection prevention and control practices. However, the influence of training hospital's infection prevention climate on nursing students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
40
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 32 publications
11
40
2
Order By: Relevance
“…These variations could be attributed to different infection prevention climate of healthcare settings. Cruz (2018) suggested that infection prevention climate is commonly understood by health care professionals pertaining to infection prevention in clinical practice. This finding is worth noting because in a descriptive study by Castro-Sánchez and Holmes (2015), the infection prevention climate differences were due to standard precautions protocol, technical procedures, human resources, infection surveillance, and standard precautions compliance assessment.…”
Section: Background Of the Studymentioning
confidence: 99%
See 4 more Smart Citations
“…These variations could be attributed to different infection prevention climate of healthcare settings. Cruz (2018) suggested that infection prevention climate is commonly understood by health care professionals pertaining to infection prevention in clinical practice. This finding is worth noting because in a descriptive study by Castro-Sánchez and Holmes (2015), the infection prevention climate differences were due to standard precautions protocol, technical procedures, human resources, infection surveillance, and standard precautions compliance assessment.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Similar to nurses, nursing students are also exposed to healthcare facilities through their clinical training (Cruz, 2018). Colet et al (2015) indicated that nursing students are involved during inpatient care in their clinical training, and they are not exempted in HAI threats (Colet et al, 2015).…”
Section: Background Of the Studymentioning
confidence: 99%
See 3 more Smart Citations